2020
DOI: 10.3389/fnbeh.2020.00145
|View full text |Cite
|
Sign up to set email alerts
|

To Approach or Avoid: An Introductory Overview of the Study of Anxiety Using Rodent Assays

Abstract: Anxiety is a widely studied phenomenon in behavioral neuroscience, but the recent literature lacks an overview of the major conceptual framework underlying anxiety research to introduce young researchers to the field. In this mini-review article, which is aimed toward new undergraduate and graduate students, we discuss how researchers exploit the approach-avoidance conflict, an internal conflict rodents face between exploration of novel environments and avoidance of danger, to inform rodent assays that allow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 64 publications
3
71
0
1
Order By: Relevance
“…Specifically, when compared to the VEH-pretreated groups, adult female mice with FLX history, spent less time in the center of the OFT and the lighted area of the LDB, while spending more time inside the closed arms of the EPM (see Figs. 2 A, 3 A, 4 A)—a behavioral response that, collectively, indicates that SSRI pretreatment mediates a long-term upward shift in baseline responses to anxiety-relevant situations 37 . Of note, these results agree with previous studies using similar behavioral tasks wherein early-life FLX induced an anxiety-like phenotype in adult male rodents 16 19 ; critically, the current work expands these findings to female mice and further explores potential biochemical mechanisms of this effect.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Specifically, when compared to the VEH-pretreated groups, adult female mice with FLX history, spent less time in the center of the OFT and the lighted area of the LDB, while spending more time inside the closed arms of the EPM (see Figs. 2 A, 3 A, 4 A)—a behavioral response that, collectively, indicates that SSRI pretreatment mediates a long-term upward shift in baseline responses to anxiety-relevant situations 37 . Of note, these results agree with previous studies using similar behavioral tasks wherein early-life FLX induced an anxiety-like phenotype in adult male rodents 16 19 ; critically, the current work expands these findings to female mice and further explores potential biochemical mechanisms of this effect.…”
Section: Discussionmentioning
confidence: 94%
“…This behavioral profile, wherein FLX rescues early-life SSRI-induced alterations to anxiety-related situations, has been reported previously in male mice 18 and rats 19 . This emphasizes that early-life antidepressant treatment renders both males and females in need of subsequent antidepressant re-exposure to normalize responses when encountering anxiety-inducing situations 37 , a critical advance considering the prevalence of mood disorders and SSRI prescription amongst females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this assay, the tendency to avoid exploring or running in the open center space (i.e. potentially dangerous) has been validated as a measure of anxiogenic behavior in mice 27 . We observed that after administering CNO, DSS-treated hM4Di-expressing mice spent a significantly greater amount of time exploring the open unprotected center zone compared to DSS-treated mCherry controls (examples in Fig.…”
Section: Resultsmentioning
confidence: 99%